Deposition of corrosion products under pressurised water nuclear reactor conditions: The effect of flow velocity and dissolved hydrogen. (October 2019) - Cassineri, Stefano; Duff, Jonathan; Cioncolini, Andrea; Curioni, Michele; Banks, Andrew; Scenini, Fabio
Highlights: CRUD build-up rate in accelerated flow regions was investigated with a microfluidic set-up. Hydrogen increased the amount of iron in solution and the radial deposition rate. CRUD deposition process occurs under mass transport control. The overall build-up rate is also affected by flow-induced mechanical removal. Higher CRUD build-up rate was observed in the low-velocity range 0–15 m/s. Abstract: The effect of water flow velocity and dissolved hydrogen on the deposition rate of Corrosion-Related Unidentified Deposit (CRUD) was investigated under conditions relevant to pressurised water nuclear reactors using type 304 l stainless steel micro-orifices. The results indicate that the CRUD build-up rate increases with hydrogen concentration because the amount of iron in solution also increases. At the same time, the fluid shear forces induce a mechanical removal of the oxide for flow velocities above 15 m/s. This suggests that the CRUD deposition process occurs under mass transport control, but the overall build-up rate is also affected by flow-induced mechanical removal.